2022
DOI: 10.1073/pnas.2117440119
|View full text |Cite
|
Sign up to set email alerts
|

Global collision-risk hotspots of marine traffic and the world’s largest fish, the whale shark

Abstract: Significance Global vessel traffic is increasing alongside world economic growth. The potential for rising lethal ship strikes on endangered species of marine megafauna, such as the plankton-feeding whale shark, remains poorly understood since areas of highest overlap are seldom determined across an entire species range. Here we show how satellite tracking whale sharks and large vessel movements globally provides a means to localize high-overlap areas and to determine how collision risk changes in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Different species of marine megafauna were not evenly protected by marine parks, with whale sharks found more frequently within moderate exposure areas in marine parks. This occurrence of whale sharks in areas with high shipping densities was also observed in Womersley et al (2022), and could be due to a lack of avoidance mechanisms of these sharks, as in some whales (McKenna et al 2015), although avoidance behaviours have been observed in odontocetes (Martin et al 2022). Although being strongly dependent on vessel design, reduced shipping speeds have been successful at lowering The movement patterns of marine giants suggest that they are exposed to shipping at over a third of the locations where tags recorded positions.…”
Section: Discussionmentioning
confidence: 72%
“…Different species of marine megafauna were not evenly protected by marine parks, with whale sharks found more frequently within moderate exposure areas in marine parks. This occurrence of whale sharks in areas with high shipping densities was also observed in Womersley et al (2022), and could be due to a lack of avoidance mechanisms of these sharks, as in some whales (McKenna et al 2015), although avoidance behaviours have been observed in odontocetes (Martin et al 2022). Although being strongly dependent on vessel design, reduced shipping speeds have been successful at lowering The movement patterns of marine giants suggest that they are exposed to shipping at over a third of the locations where tags recorded positions.…”
Section: Discussionmentioning
confidence: 72%
“…A single population is easier to conserve, but the international movements exhibited by some individuals in this study mean that cooperation between Red Sea countries may be necessary for protection to be effective (Gajdzik et al, 2021). Additionally, recent evidence suggests that cargo ship strikes could be an under‐reported and significant contributor to whale shark mortality (Womersley et al, 2022). A high degree of surface occupation (Andrzejaczek et al, 2021) and the frequent movements of oceanic manta rays across one of the busiest shipping lanes in the world may also make this species vulnerable to similar threats (Braun, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Higher speed swimming (derived by using trigonometry on body pitch and vertical velocity) was also highlighted on occasion in individual whale sharks by short-term substantial PPA min values both for descents (e.g., Figure 5 B) and ascents although the reasons for them doing this are unclear. We speculate that the animals were either reacting to vessels or other perceived threats and inspection of where these events occurred may prove useful for conservation reasons ( Womersley et al., 2022 ).
Figure 4 PPA min at different depths A dive by a whale shark between periods swimming at the surface, showing depth (blue line) and vertical velocity (yellow line) and the proxy for power above the minimum (PPA min ) (black line).
…”
Section: Discussionmentioning
confidence: 99%